The Role of 'Aisyiyah in Women's Empowerment through the Sakinah Family Study Program: A Case Study of PCA Kanor, Bojonegoro Regency - Lina Alfiah; Benny Prasetya; Nur Mashani Mustafidah (Immortalis Journal of Interdisciplinary Studies, 2026)
'Aisyiyah, a women's organisation within Muhammadiyah, plays a strategic role in promoting women's empowerment and strengthening family resilience through Islamic values. This study aims to explore the role of 'Aisyiyah in empowering women through the Sakinah Family Study Program implemented by the 'Aisyiyah Branch Leadership (PCA) of Kanor, Bojonegoro Regency. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis involving PCA leaders, cadres, and programme participants. The findings reveal that the programme contributes to enhancing women's religious understanding, improving family communication and conflict-resolution skills, promoting economic empowerment through community-based entrepreneurship, and strengthening family resilience through the implementation of the principle of mu'asyarah bil ma'ruf. The programme also increases women's self-confidence and participation in community activities. These findings indicate that grassroots Islamic women's organisations can function as effective agents of social transformation by integrating religious education with women's empowerment initiatives. This study contributes to the growing literature on faith-based community empowerment and family resilience in contemporary Muslim societies.